Early Detection of Financial Reporting Fraud in State-Owned Banks: The Role of Good Corporate Governance Mechanisms with the F-Score Model - Elly Suryani; Wenden Tebila (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to determine the effect of Good Corporate Governance (GCG) mechanisms on indications of financial statement manipulation in the banking sector of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) for the 2017–2023 period. GCG is measured by three indicators, namely external audit, audit committee effectiveness, and independent board of commissioners using the F-Score method. The sampling technique used in this study is purposive sampling with a sample of 4 SOE banks or 28 data on SOE companies listed on the Indonesia Stock Exchange in 2017–2023. The data used are secondary data obtained from the company's annual report and the official BEI website. This research method uses a quantitative method and the analysis uses logistic regression analysis using IBM SPSS 26. The results of the study indicate that GCG, namely, external audit, audit committee effectiveness, and independent board of commissioners have a simultaneous effect on indications of financial statement manipulation of SOE banks with the help of control variables, namely company size and leverage. In addition, external audit, audit committee effectiveness, and independent board of commissioners partially do not affect indications of financial statement manipulation of SOE banks. These findings indicate that the implementation of effective corporate governance collectively has an important role in reducing the potential for financial reporting manipulation in the state-owned banking sector.